Leadership, teamwork and person-organization fit as determinants of job satisfaction: a case survey among public sector employees / Siti Farhana Hasanudin ... [et al.] - Hasanudin, Siti Farhana; Nik Abdullah, Nik Azlina; Ibrahim, Ima Ilyani; Mahmud, Luqman (Faculty of Business and Management ; UiTM Press, 2024)
Employee and job satisfaction has been the primary research topic in management studies worldwide. It is the primary concern for organisations to measure the performance of individuals by how they carry out their responsibilities in a manner that contributes to the achievement of the organisation's goals and creates satisfaction in their work. This study examines the relationship between leadership, teamwork, and the fit of person-organisation on job satisfaction. Employees at the Department of Statistics Malaysia were taken as the respondents in this study. The self-administered questionnaire was used for the collection of data. Two hundred questionnaires were distributed among the organisations mentioned above, and 108 responses were returned, so the response rate was 54%. The result concludes a significant relationship between leadership teamwork and job satisfaction; meanwhile, person-organization fit is insignificant. This study put forth several recommendations for the organisation to promote job satisfaction and recommendations for future research.